2016
DOI: 10.1038/cdd.2016.20
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell survival during angiogenesis requires the pro-survival protein MCL1

Abstract: Angiogenesis is essential to match the size of blood vessel networks to the metabolic demands of growing tissues. While many genes and pathways necessary for regulating angiogenesis have been identified, those responsible for endothelial cell (EC) survival during angiogenesis remain largely unknown. We have investigated the in vivo role of myeloid cell leukemia 1 (MCL1), a pro-survival member of the BCL2 family, in EC survival during angiogenesis. EC-specific deletion of Mcl1 resulted in a dosedependent increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 47 publications
1
30
0
1
Order By: Relevance
“…Consistent with previous reports (Simonavicius et al, 2012;Watson et al, 2016), we found that apoptosis was predominantly located around arteries at postnatal day (P) 6, with a limited amount around the veins and almost none in the sprouting region (Fig. 1A,B).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with previous reports (Simonavicius et al, 2012;Watson et al, 2016), we found that apoptosis was predominantly located around arteries at postnatal day (P) 6, with a limited amount around the veins and almost none in the sprouting region (Fig. 1A,B).…”
Section: Resultssupporting
confidence: 92%
“…Our data argue against a role for apoptosis promoting vessel regression during angiogenesis. Furthermore, mice with EC-specific loss of the pro-survival protein MCL1 exhibited a far greater increase in apoptosis than that reported for mice lacking non-canonical Wnt, but did not show an increase in vessel regression (Watson et al, 2016). These findings would argue against a role for apoptosis in promoting vessel regression, even when ectopically activated.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations